Determinação experimental e modelagem da tensão superficial, densidade e velocidade do som de sistemas aquosos contendo sais orgânicos - Costa, Paula Renée de Macêdo (2020)
Organic salts have been industrially applied in drugs as lubricants, excipients or active ingredients; in textiles, they have used as a reducing agent; and mainly on the food industry, where they have been used as chemical preservatives. The main class of these salts is obtained from the carboxylic acid, which present organic electrolytes. The problem of dealing with electrolytes solutions is due the thermodynamic properties are influenced by the types of cations and anions, which present long-range interactions that happen even at low concentrations. Classical models are not able to modeling the phenomenological behavior of this kind of system. To overcome this problem, the addition of adjustments terms that consider the interactions between ion-ion and solvent-ion pairs have been proposed. The Debye-Hückel limiting law can represent in a reasonable way the behavior of very dilutes electrolytes solution – approximately up to 0.01 mol•kg-1. From this law, several physical models have been developed with the intent to extend this range of application. Pitzer modeling is one that stands out for being applicable to wide ranges of composition, temperature and pressure. Beyond that, based on the condition of equilibrium between surface and bulk phases, this model can provide estimates of surface tension, from the equations of the osmotic coefficient of solution. From the derivatives with respect to pressure of Pitzer’s equation of osmotic coefficient, it is possible calculate volumetric properties of the mixture. In this work, we measured the surface tension, density and speed of sound of the aqueous solutions of the following salts of sodium: formate, acetate, propionate, and benzoate, offering a wide database of properties to the literature. From these values, we evaluated the models based on Debye-Hückel limiting law, including the Pitzer equation and its derivatives, for the modeling of the measured properties.